Determining the approaches to learning mathematics of middle school students [Ortaokul öğrencilerinin matematik öğrenme yaklaşımlarının belirlenmesi1] - ÖZDEMİR, AHMET ŞÜKRÜ (Ankara University, 2018)
The aim of this research was to develop an instrument for determining the approaches to learning mathematics of middle school students. This research was a scale development study and presented the validity and reliability studies of the Approaches to Learning Mathematics Scale as well as a descriptive study and investigated the learning approaches of students. The participants were 790 middle school students. Exploratory factor analysis revealed three factors for students' approaches to learning: deep, surface and strategic. Confirmatory factor analysis confirmed that these three factors constituted a model-with good fit. The Cronbach’s alpha reliability coefficient for the whole of the scale was found to be.789. The results showed that Approaches to Learning Mathematics Scale, consisting of 33 items and 3 factors, was a valid and reliable scale. In addition, findings indicated that there were significant differences between the students’ approaches to learning mathematics according to their grade levels. © 2019, Ankara University. All rights reserved.
Keywords: Approaches to learning mathematics; Middle school students; Reliability; Scale development; Validity